How cost-effective is biofortification in combating micronutrient malnutrition? An ex ante assessment - Meenakshi, Jonnalagadda V.; Johnson, Nancy; Manyong, Victor M.; De Groote, Hugo; Javelosa, Josyline; Yanggen, David; Naher, Firdousi; González, Carolina; García, James; Meng, Erika (International Food Policy Research Institute, 2010)
Biofortification is increasingly seen as an additional tool to combat micronutrient malnutrition. This paper presents, for the first time, evidence on the costs and potential benefits of biofortification for a large number of countries in Africa, Asia and Latin America. We use a modification of the Disability-Adjusted Life Years framework to conclude that the intervention can make a significant impact on the burden of micronutrient deficiencies in the developing world, and can do so in a highly cost-effective manner.